UPAYA PENGELOLAAN LAHAN BANGUNAN PADA BANTARAN SUNGAI BERBASIS LINGKUNGAN DI KABUPATEN SLEMAN DIY - Mulyandari, Hestin (Semarang State University, 2011)
Sleman district have many good lands for investment, cause price of land would be raised, so that people look for the area increasingly. Eventually affect the increase land using in flood plains area in Sleman district as a reason of cheap land. From various studies that have been done, which flooding occurs in areas prone basically due to three factors, namely: human activities, natural events and environmental degradation. This study aims to direct the management of flood plains area better. This research was conducted by exploration to find using river bank and evaluate policy and control mechanisms in the areas of space utilization riverbanks in Sleman district. the case study of river are: Boyong-Code river, Winongo river, and Gadjah Wong river. Generally, the drainage concept of the three rivers are still referring to the concept of conventional drainage. The concept was interpreted as a run off water as soon as possible to the river and further downstream. Even the conventional drainage is often interpreted as an effort to drying area. The concept must be changed with the concept of environmentally friendly toward the drainage, for example run off water into a river naturally. It is therefore necessary to overcome the floods with the application of the concept: